Working in the Islamic economy: sharia-ization and the Malaysian workplace - Sloane-White, Patricia (Sojourn, 2011)
This article demonstrates how sharia, the source for developing products in Malaysia’s Islamic economy, has also emerged in some Malaysian businesses as a form of corporate culture, reconfiguring workplace identities and social relations. It takes the form of what I call “corporate sharia”, a set of ideas consciously and deliberately shaped by executives who seek to build corporations based on the rules for commerce and management contained within the Qur’an and Hadith. Corporate leaders also fashion what I call “personnel sharia” - “human resources” rules to ensure that employees exhibit the ethical values and moral principles set by their superiors. As such, the “Islamic workplace” becomes sharia-ized, where the piety and Islamic subjectivities of personnel are shaped, monitored, and enforced, not left to individual, personal choice. (Sojourn/GIGA)